Uso da linguagem OCL no contexto de diagramas de classe da UML e programas em java - Vinicius Coelho de Almeida (2006)
In this work, we present OCL usage in forward engineering of UML class diagrams to Java code, as well as a discussion of its potential usage during reverse engineering in this context. The stateof-art of the related tools in the academic literature, and existing problems on forward and reverse engineering were surveyed. Also, we have identified mappings among types and operations from both languages. Finally, our conclusions about OCL usage viability on development process andproposal of future works finalize the dissertation.